The impact of cultural differences and absorptive capacity on Chinese acquiring firms' post-acquisition integration: an exploratory qualitative study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Management at Massey University, Albany, New Zealand - Zhao, Muzhi (Massey University, 2018)
Cross-border mergers and acquisitions (M&As) have shown significant growth during recent years. In particular, Chinese cross-border M&As have captured an important position. However, the failure rate has continued to be noteworthily high, while cross-border M&As have increased significantly. Also, previous research indicated problematic characteristics of a lot of Chinese cross-border M&As. The research, which has focused on the post-acquisition integration of Chinese cross-border M&As, is still emerging and understudied. Therefore, this study aims to investigate further insights on the impact of cultural differences and absorptive capacity on the post-acquisition integration mode of Chinese acquiring firms in Chinese cross-border M&As within developed economies. A total of 16 senior managers from three Chinese medium-high-technology manufacturing enterprises have participated in a semi-structured face-to-face interviews in their offices in three different cities in China; Ningguo, Beijing, and Taiyuan. The interviews were undertaken over a six-week period from October to November in 2016. All the interviews have been transcribed verbatim and thematically analysed manually after the data collection phase. This study found four motivations for Chinese acquiring firms to attempt cross-border M&As. Subsequently, since three main obstacles were discovered; cultural differences, perceived environmental uncertainty and lack of managerial confidence, and weak absorptive capacity; Chinese acquiring firms have adopted a ‘Wu Wei, Selective You Wei, & Reversed You Wei’ integration mode in the post-acquisition integration to avoid the influence of these obstacles as much as possible, and assimilate and integrate the newly acquired knowledge from their acquired firms effectively.
Keywords: Consolidation and merger of corporations -- China -- Case Studies; Organizational change -- China -- Management -- Case studies